The Effect Of Third Party Funds (DPK), Non Performing Financing (NPF), And Indonesian Sharia Bank Certificates (SBIS) On Sharia Banking Financing Distribution In Indonesia - Riyan Pradesyah; Yuyun Triandhini (Research Collaboration Community (RCC), 2021)
The purpose of this research is to determine the effect of DPK, NPF, and SBIS either partially or simultaneously on the distribution of Islamic banking financing in Indonesia. In this research , using quantitative methods and the type of data used is secondary data. The sample used in this study is data on total financing, DPK, NPF and fund placement in Islamic Commercial Bank SBIS which are contained in the monthly Islamic Banking Statistics published by the Financial Services Authority for the period 2015 - 2019. The data analysis technique used in this study is test classical assumption, multiple linear regression and hypothesis testing. The results of this study were processed in the SPSS 22 program.The results showed that partially (t test) the DPK variable had a positive effect on the distribution of financing. This was evidenced by the t count (56.185)> (1.67252) t table and the sig value. 0.000 < 0.005. The NPF variable has a negative effect with t count (-3.914) <(1.67252) t table and sig. 0.000 < 0.005. The SBIS variable has no effect, as evidenced by the t count (1.536) <(1.67252) t table and the sig value. 0.130 > 0.005. Taken together (F test) shows that DPK, NPF, and SBIS have a significant effect on financing distribution as evidenced by the value of F count (1565,122)> (2.77) F table and sig. 0.000 < 0.005. The adjusted R2 value is 0.988, which means that the DPK, NPF and SBIS variables affect the distribution of financing by 98.8% while the remaining 1.2% is influenced by variables outside of this research .